Analisis Kepuasan Terhadap Pelayanan Supplier Menggunakan Metode A New Additive Ratio Assessment (ARAS) - Agung Deni Wahyudi (PT. Tech Cart Press, 2024)
Analysis of company satisfaction with supplier services is a critical step in maintaining a sustainable relationship between the company and its suppliers. Problems experienced in customer service satisfaction there is no model that can assess company satisfaction in terms of service from suppliers. Thus, the analysis of company satisfaction with supplier services is not only an evaluation instrument, but also an important strategy in achieving competitive advantage through effective and sustainable supply chain management. The purpose of this study is to measure the level of company satisfaction with supplier services by applying the ARAS method which will produce a decision in the form of a final ranking of company assessment data on supplier services. The final ranking results show satisfaction with the highest supplier service obtained by the name of the Berkah Sejahtera supplier with a final value of 0.9384 getting rank 1, then the name of the Harmoni supplier with a final value of 0.9359 getting rank 2, then the name of the supplier Indah Karya with a final value of 0.9106 getting rank 3.